Bioconversion of ω-fatty acids extracted from giant snakehead and mudskipper fish oils - Omar, Muhammad Nor; Che Othman, Siti Fairuz; Md Yusoff , Nur Shahidatul Ahlam; Zainuddin, Nur‘Aziyah; Mohamad Talib, Hasan; Yunus, Kamaruzzaman (2009)
Studies on bioconversion of ω-fatty acids in giant snakehead and Mudskipper fish oils were carried out using guinea pig lung homogenate. The oils, after conversion into their fatty acids, were incubated aerobically at 37oC in phosphate buffer solution with the addition of guinea pig lung homogenate. After incubation it was found that ca. 76% arachidonic acid has been converted to the prostaglandin metabolite. The fatty acid constituents in fish oils were analysed by GC-MS after interesterification